EVALUATION OF ANALGESIC ACTIVITY OF AQUEOUS EXTRACT OF LEAVES OF SOLANUM MELONGENA LINN IN EXPERIMENTAL ANIMALS - Ms, UMAMAGESWARI; Maniyar, Yasmeen A (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The present study was aimed to find out the central and peripheral analgesic activity of aqueous leaf extract of Solanum melongena Linn (AESML) in experimental animals. Methods: Preliminary phytochemical analysis of AESML was performed by chemical tests. The central analgesic activity was measured by tail flick method in Wistar rats and peripheral analgesic activity was measured by acetic acid induced writhing in Swiss albino mice. Aspirin was used as the standard drug in the dose of 300 mg/kg b.w. in tail flick method and 100 mg/kg b.w. in acetic acid induced writhing test. Results: Phytochemical analysis showed the presence of flavonoids, alkaloids, glycosides, saponins, tannins, sterols, carbohydrates, and resins. The aqueous extract was administered at 100 mg/kg, 200 mg/kg, 400 mg/kg b.w. All the doses showed significant central and peripheral analgesic activity (p<0.001), which is comparable to that of the standard drug aspirin. Conclusion: AESML leaves has both central and peripheral analgesic activity. Keywords: Solanum melongena Linn, Aqueous extract, Analgesic activit